SLC40A1-related hemochromatosis associated with a p.Y333H mutation in mainland China: a pedigree report and literature review - Yue Li; Fangfang Duan; Song Yang (BMC, 2024)
Abstract Background Haemochromatosis is a genetic disease characterized by the excessive deposition of iron in various tissues and organs, eventually results in organ damage including cirrhosis, diabetes, cardiomyopathy, etc. SLC40A1-related haemochromatosis is associated with gain-of-function mutations in the SLC40A1 gene, which encodes ferroportin. While sporadic reports of this condition exist in mainland China, the understanding of the phenotype and genetic pattern associated with the SLC40A1 p.Y333H mutation remains incomplete. Case presentation We report a pedigree with heterozygous p.Y333H mutation in Chinese Han population. The proband is a 64-year-old man complaining of persistent abnormality of liver enzyme levels for 1 year, with a history of knee joint pain, diabetes and skin pigmentation. He displayed markedly elevated serum ferritin level and transferrin saturation. Magnetic resonance imaging showed iron deposition in the liver, spleen, and pancreas, along with cirrhosis and splenomegaly. Whole exome sequencing identified a heterozygous allelic variant c.997T > C (p.Y333H). Genetic screening of family members identified four first-degree relatives and three second-degree relatives having the same mutation. Additional cases with this mutation from two published studies were included. Among the probands and screened relatives, all eight males aged over 30 y had ferritin level > 1000 µg/L, transferrin saturation > 90%. Four patients with organ damage in the present study received therapeutic phlebotomy, alleviating clinical symptoms and improving in transferrin saturation and serum ferritin. Conclusions This study reports the largest pedigree with heterozygous SLC40A1 p.Y333H mutation in the Chinese population to date. In Chinese families, males over 30 years old with hemochromatosis due to SLC40A1 p.Y333H mutation exhibit severe iron overload phenotypes.